The AP-1 transcription factor JunB is essential for multiple myeloma cell proliferation and drug resistance in the bone marrow microenvironment - Fan, Fengjuan; Bashari, Muhammad Hasan; Malvestiti, Stefano; Vallet, Sonia; Seckinger, Anja; Hose, Dirk; Ball, Claudia R.; Glimm, Hanno; Goldschmidt, Hartmut; Jäger, Dirk; Podar, Klaus (Leukemia, 2017)
Despite therapeutic advances, multiple myeloma (MM) remains an incurable disease, predominantly because of the development of drug resistance. The activator protein-1 (AP-1) transcription factor family has been implicated in a multitude of physiologic processes and tumorigenesis; however, its role in MM is largely unknown. Here we demonstrate specific and rapid induction of the AP-1 family member JunB in MM cells when co-cultured with bone marrow stromal cells. Supporting a functional key role of JunB in MM pathogenesis, knockdown of JUNB significantly inhibited in vitro MM cell proliferation and survival. Consistently, induced silencing of JUNB markedly decreased tumor growth in a murine MM model of the microenvironment. Subsequent gene expression profiling revealed a role for genes associated with apoptosis, DNA replication and metabolism in driving the JunB-mediated phenotype in MM cells. Importantly, knockdown of JUNB restored the response to dexamethasone in dexamethasone-resistant MM cells. Moreover, 4-hydroxytamoxifen-induced activation of a JunB-ER fusion protein protected dexamethasone-sensitive MM cells against dexamethasone- and bortezomib-induced cytotoxicity. In summary, our results demonstrate for the first time a specific role for AP-1/JunB in MM cell proliferation, survival and drug resistance, thereby strongly supporting that this transcription factor is a promising new therapeutic target in MM.